Peran Akreditasi Sekolah Dalam Meningkatkan Mutu Pendidikan di SDIT Adzkia 1 Sukabumi - Najrul Jimatul Rizki; Siti Qomariyah; Neneng Neneng (Institut Nalanda, 2024)
Education is an important part in efforts to save the generation of the Indonesian nation to be better and brighter in the future. Therefore, the government continues to strive to continue to improve the quality of our education, one of which is by conducting school accreditation. Which accreditation aims to maintain the quality or standard of education in every institution, foundation or educational institution. This study aims to determine the role of school accreditation in improving the quality of education at SDIT Adzkia 1 Sukabumi. Accreditation is an evaluation process that aims to ensure that schools meet the established educational standards. Using a qualitative approach, this study examines the impact of accreditation on various aspects of education at the school, including teaching quality, school management, and community involvement. The results of the study indicate that accreditation plays a significant role in driving continuous improvement at SDIT Adzkia 1 Sukabumi. The accreditation process helps schools identify strengths and weaknesses, improve teacher professionalism, and strengthen management and governance. In addition, accreditation also increases the trust and participation of parents and the community, which contributes to improving the overall quality of education. This study concludes that accreditation not only functions as an evaluation tool, but also as a major driver for achieving higher quality education. Suggestions provided include improving teacher training, strengthening facilities and infrastructure, and increasing parental and community involvement in the education process.